DUKUNGAN SOSIAL DENGAN TINGKAT STRES MAHASISWA KEPERAWATAN SELAMA PEMBELAJARAN ONLINE DI MASA PANDEMI COVID-19 - Yuhbaba, Zidni Nuris; Budiman, M.Elyas Arif; Sya'id, Achmad; Ayasah Pratita Kirana (Universitas Sam Ratulangi, 2024)
Background :The Covid-19 pandemic has had an impact on the world of education, namely the change in online learning methods implemented by the government has caused students to experience academic stress. Social support is one way to reduce students' academic stress levels during online learning. Aim :The aim of this research is to determine the relationship between social support and students' academic stress levels during online learning during the Covid-19 pandemic. Methods :The method used was a cross sectional design and a research sample of 235 respondents using the Stratified Random Sampling technique. This research was conducted online using a social support instrument, namely the MSPSS (Multidimensional Scale of Perceived Social Support) questionnaire and an academic stress level instrument, namely the PASS (Perception of Academic Stress Scale) questionnaire. Data analysis uses Spearman rank correlation. Results :The results of this research show that p < 0.05 with a significant value of p = 0.00 and a correlation coefficient (r) = -613 so that there is a relationship between social support and students' academic stress levels which protect them during online learning during the Covid-19 pandemic. Covid-19 with a strong correlation between the 2 variables. Conclusion : Social support obtained from parents, friends and special people has an important role and positive influence on reducing academic stress levels in students during online learning during the Covid-19 pandemic.